Hands on My Hips: Politics of a Subversive Fish. (April 2016) - Teman, Eric D.
These interpretive autoethnographic tales are about my life experiences, growing up in rural Ohio as a queer male. I relive several of the innumerable unfortunate encounters with bullies who have haunted me over the years, partly as a therapeutic means to cope with the lasting effects of those torturous years and partly to potentially reach and touch the lives of others similarly affected. I use performative texts as a powerful means of portraying and articulating my message and persuasively voicing the emotion experienced. I also reflect on the queer predicament and how it has shaped my life.